Penerapan Stabilisasi Dengan Kapur Dan Abu Sekam Untuk Meningkatkan Daya Dukung Dan Memperkecil Swelling Pada Subgrade Konstruksi Jalan - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Risman, Warsiti, Martono, Mawardi (Teknis, 2014)
Soil with a high value of shrinkage, the water is very influential on physical and mechanical behavior of the soil (Das, 1994). Expansive clay generally have less favorable properties such as low dry density (gdmax), low California Bearing Ratio (CBR), low shear strength, and tall swelling. Nature is what causes the often broken pavement repairs even though frequent pavement structure. Road conditions in the Sendang Mulyo also experiencing the same thing that is quickly damaged although often performed repairs on the road surface layer. To problem solve these issues one way or the method used is to improve the quality of the original soil (stabilization). This research was conducted to find out more about the effect.Â  of stabilizing agent husk ash with lime and magnitude of the carrying capacity (CBR), and swelling soil. Laboratory testing includes test compaction, CBR and soil swelling. Addition of rice husk ash percentage varies from 5%, 10%, 15% and 20%. While the addition of lime percentage varies from 5%, 8% and 10%. In the research showed that the addition of lime and rice husk ash clay has a tendency to increase the density of the soil, good soil CBR value on condition without soaking or by immersion, and can reduce swelling soil. This condition occurs in clay mixed with rice husk ash 20% and 10% limestone which produces CBR value of 20.86% and 1.59% swelling.Keywords: stabilization, compaction, CBR, Swell